Performance of solar PV-fuel cell (FC) hybrid system for stand-alone applications - Ramesh, T; Dharunprasath, L; Kaliappan, S; Emayavaramban, G (International Journal of Engineering and Technology, 2018)
This paper presents the performance of a hybrid solar PV/ Fuel Cell/ FC system with a PMDC motor load. The hybrid system supplies power to the DC motor during day and night. In order to obtain continuous supply to the load, a control strategy is implemented in the system. By using this control strategy, the solar PV and the fuel cell supply the voltage to the load by getting constant supply from the DC link during day and night. The DC-DC interleaved soft switching boost converter (ISSBC) with Incremental conductance maximum power point tracking technique (INC MPPT) is used to maintain constant DC link voltage. When the power deficit happens in the solar PV, the hydrogen stored in the tank is used by the fuel cell stack and supplies power to the load. The entire system is modeled and the performance of the hybrid system is analyzed in MATLAB/Simulink environment.Â Â